Improving Senior High School Studentsâ Mathematical Communication Ability Through Generative Learning In Bengkalis Regency - Hutapea, Nahor Murani (Proceedings of the UR International Conference on Educational Sciences, 2018)
Mathematical communication ability (MCA) is an ability required by each individual to cope all life challenges. However, studentsâ MCA has in fact not yet well-developed up to senior high school level. Generative learning (GL) is considered able to elicit the development of studentsâ MCA. This research aims to examine studentsâ MCA through the implementation of GL. The type of this research is quasi experiment with pretest and postest control group design. The research subject was students of grade X from three public senior in Bengkalis Regency i.e. Bengkalis SMAN-1, Mandau SMAN-1 and Pinggir SMAN-1. The research used a set of MCA test. Data analysis employed t-test (equal variences assumed). The research result shows that (1) GL could better achieve studentsâ MCA compared to the control class sample with conventional learning method (CLM), Bengkalis: 10.58 > 8.47, Mandau: 9.47 > 8.18, Pinggir: 7.36 > 6.35, and (2) GL could better enhance studentsâ MCA compared to the control class sample with CLM, Bengkalis: 0.79 > 0.61, Mandau: 0.69 > 0.58, Pinggir: 0.52 > 0.43. Improving of studentsâ MCA throgh GL in Bengkalis was high, but for Mandau and Pinggir, both GL or CLM were moderate.